Patient willingness to undergo a two‐week free trial of a telemedicine service for coronary artery disease after coronary intervention: A mixed‐methods study. (21st February 2020) - Lin, Yueh‐Hsiu; Huang, Guey‐Shiun; Ho, Yi‐Lwun; Lou, Meei‐Fang
Abstract: Aim: To understand the factors affecting willingness to use telemedicine in patients with coronary artery disease after coronary intervention. Background: Telemedicine is a relatively new service provided to discharged patients in Taiwan, therefore, public acceptance is low. Method: This mixed‐methods study conducted between January and June 2014 used convenience sampling. In total, 140 patients were offered a two‐week free trial of telemedicine services before hospital discharge. Participants completed structured questionnaires and answered semi‐structured qualitative questions related to willingness to use telemedicine services. Results: Patients' willingness to use telemedicine was not significantly correlated with experience using technology, perceived ease of use or computer self‐efficacy; instead, it was based on trust in the hospital staff, opinions of the staff and ongoing support from the case manager. Reasons for their lack of willingness to use the service were mainly related to diseases, technology/equipment and environmental factors. Conclusion: Staff support through telephonic tracking and real‐time feedback can increase willingness to use telemedicine. Implications for Nursing Management: Case managers can collect necessary personal information and offer the patients 24‐hr services as a monitor, an instructor and a companion, thereby accommodating more patients, building value and strengthening telemedicine services.